Consecutive case series of 244 age-related macular degeneration patients undergoing implantation with an extended macular vision IOL. Issue 2 (March 2018) - Qureshi, Muhammad A.; Robbie, Scott J.; Hengerer, Fritz H.; Auffarth, Gerd U.; Conrad-Hengerer, Ina; Artal, Pablo
Purpose: To determine safety and visual outcomes in eyes with age-related macular degeneration (AMD) implanted with a novel intraocular lens (IOL) that delivers an optimized retinal image to all macular areas within 10 degrees of retinal eccentricity. Methods: This was a consecutive case series of 244 eyes with dry/stable wet AMD and logMAR visual acuity ≥0.3 implanted with iolAMD Eyemax mono TM (London Eye Hospital Pharma), a single-piece, injectable, hydrophobic acrylic IOL sited in the capsular bag. Primary outcome was safety. Secondary outcomes were changes in corrected distance visual acuity (CDVA) and corrected near visual acuity (CNVA) (logMAR). Results: Mean age at surgery was 80 years. Mean duration of follow-up was 3 months (range 1-16 months). No eyes had worsening of CDVA. Frequency of perioperative complications was equivalent to standard IOL implantation. Postoperative refractive outcomes were within ±1 D of the target refraction in 88% of cases. Mean preoperative CDVA improved from 1.06 to 0.71 postoperatively (mean of differences -0.35; 95% confidence interval [CI] -0.3886 to -0.3223; p<0.0001), equating to an approximate Early Treatment Diabetic Retinopathy Study gain of 18 letters. Mean preoperative CNVA (N-point; logMAR conversion) improved from 1.36 to 0.88 postoperatively (mean of differences -0.48; 95% CI -0.53 to -0.44; p<0.0001). Conclusions: This novel IOL appears safe in the short to medium term. Improvements in postoperative CDVA and CNVA exceed those observed with standard implants.